Comparative Study of Effects of Vonoprazan and Esomeprazole on Antiplatelet Function of Clopidogrel or Prasugrel in Relation to CYP2C19 Genotype. Issue 5 (13th October 2017) - Kagami, Takuma; Yamade, Mihoko; Suzuki, Takahiro; Uotani, Takahiro; Hamaya, Yasushi; Iwaizumi, Moriya; Osawa, Satoshi; Sugimoto, Ken; Umemura, Kazuo; Miyajima, Hiroaki; Furuta, Takahisa
Abstract : Drug–drug interaction between antiacid and antiplatelet agents has not been fully elucidated. Vonoprazan, a new potassium competitive acid blocker, has been available in Japan. CYP2C19 and CYP3A4 are involved in the metabolism of clopidogrel, prasugrel, esomeprazole, and vonoprazan. Using a P2Y12 assay, we compared the effects of vonoprazan and esomeprazole on the antiplatelet functions of clopidogrel or prasugrel in 31 healthy Japanese volunteers (14 CYP2C19 homo‐extensive (homo‐EMs), nine hetero‐extensive (hetero‐EMs), and eight poor metabolizers (PMs)). Vonoprazan decreased the median inhibition of platelet aggregation (IPA) values of clopidogrel and prasugrel more potently than esomeprazole ( P < 0.001 for clopidogrel and P = 0.011 for prasugrel). The same tendencies were observed when stratified by CYP2C19 genotype groups ( P = 0.004 in homo‐EMs, 0.033 in hetero‐EMs, and 0.043 in PMs). Vonoprazan attenuated the antiplatelet function of clopidogrel more potently than esomeprazole. Esomeprazole did not affect that of prasugrel irrespective of CYP2C19 genotype.